OC-075 Impact of pre-existing biliary stents on eus staging in patients with a head of pancreas mass. (17th June 2017) - Bekkali, NL; Nayar, MK; Johnson, SJ; Thornton, L; Darne, A; Haugk, B; Leeds, J; Charnley, RM; Oppong, KW
Abstract : Introduction: Self-expanding metal stents (SEMS) are superior to plastic stents (PS) for pre-operative drainage of the common bile duct (CBD) and are increasingly preferred. Endoscopic ultrasound (EUS) has a role in staging particularly of tumours that are borderline operable on CT. Biliary stents can cause acoustic shadowing and artefacts thereby reducing the view of the posterior aspect of the tumour and its relationship to local vessels. SEMS have a larger cross-sectional profile and may cause more shadowing than PS. There are to date no published studies of the impact of biliary stents on EUS staging. The aim of this study is to assess whether the presence of a biliary stent impairs the accuracy of linear EUS staging. Method: The study group comprised all patients with head of pancreas (HOP) mass undergoing EUS biopsy between January 2013 and June 2016. Staging information was obtained from the EUS report. Staging was considered accurate when EUS had the same staging with respect to the major vessels (SMV, SMA and PV) as per outcome of surgery or multidisciplinary consensus following imaging review. Any statement indicating inability to fully image the tumour margins due to stent was classified as indicative of inaccurate staging. Accuracy of vascular staging between the stented and unstented group was analysed using Chi-square test. Results: A total of 835 patients underwent EUS for a solid pancreatic mass of which 382 had a mass in the HOP. Median age was 67 [25-86] yrs and 326 (85%) were male. At time of EUS, 232 of 382 (61%) patients had no stent and 150 (39%) patients had stents in the CBD; 97 (65%) SEMS and 53 (35%) PS. Staging wasn't required in 74 patients and reports were not available in 14; 260 had documented EUS staging. Overall staging accuracy was 247/297 (83%); accurate in 39/76 (51%) SEMS patients, 37/43 (86%) with PS and 171/178 (96%) unstented patients. Staging outcomes were significantly different between SEMS compared to the PS group (p=0.0003) and the unstented group, p=0.0001. Difference in staging between plastic stent and the unstented group was also significant, p=0.03. Conclusion: Our results show a significant impact of SEMS and plastic stents on EUS staging. The effect is greatest with SEMS. We therefore recommend that patients in whom EUS staging is indicated, who also require biliary drainage, should have EUS performed before stent placement and if biliary drainage must be performed before EUS, plastic stents should be considered. Disclosure of Interest: None Declared